Sociolinguistic conotation of the term “chimerical groups” in school - Tsankov, Nikolay; Guyviiska, Veska (Special Education, 2017)
Chimerical groups at school are a new pedagogical reality observed in the behavior of communities prone to deviant activities. The different interpretations link these communities to difficult children, youth subcultures, and street gangs while chimerical groups are a possible conceptual projection on them. We are attempting at a sociolinguistic reading of the term “chimeric group at school” as a community off children and adolescents with deviant behavior but not juvenile offenders, which makes us face legal terms and delinquent behavior. A chimerical group of dealers, pimps, prostitutes and other subjects with deviant behavior at school imitates the behavior of criminal groups in society, borrowing mechanisms and means and also creating their own ones through social networks. The studying of the sociolinguistic connotations of the term “chimeric group” allows the estimation of the preparedness of the pedagogical community to adequately perceive this phenomenon and deal with it accordingly.
Keywords: chimerical group; institutional community; behavior; social and linguistic parameters; verdicts; speech acts; performative act; successful communication